Factors related to intention to stay among gen Y in Malaysian manufacturing companies - Syahrulniza, Anak Lembang (2015)
This study examines the direct relationship between human resource practices such as training and development, compensation and benefits, career development and performance appraisal, perceived organizational support, leadership style such as transformational, transactional and laissez-faire and intention to stay. A total of 400 questionnaires were disributed to participants who had agreed to participate in this study. However, only 200 questionnaire were returned and usable for further analyses. Hypotheses for direct effect were tested using multiple regression analyses. Results showed that only training and development, compensation and benefits, and transformational leadership style were significantly positively associated with intention to stay. Implications of the findings, potential limitations, and directions for future research are discussed.